Anode-Free High Volumetric Energy Density Solid-State Lithium Microbatteries - Yang, Hui; Wang, Zhongchun; Pirzada, Shahid; Yan, Alex; Rao, Shoba; Paul, Nihal; van der Linde, Richard; Tu, Jay; Kamath, Arvind (Meeting abstracts (Electrochemical Society), 2025)
All-solid-state thin-film microbatteries with anode-free architecture provide high volumetric energy density, fast charging, safety, surface-mount technology (SMT) compatibility, and long cycle life. Typically, large interfacial resistances and low ionic conductivity of solid-state electrolytes are critical issues which have hindered its commercialization. In this work, interface engineering between collector and electrode, electrode and electrolytes have been systematically optimized to achieve low impedance interfaces, enabling fast charge and high pulse rate discharge. Additionally, optimized design of anode current collector has induced uniform lithium (Li) nucleation and homogeneous Li deposition, effectively suppressing Li dendrite formation. We demonstrate environmentally friendly scalable manufacturing of stacked thin-film microbatteries with high volumetric energy density and high pulse discharge C-rates, which are highly valued by space-constrained hearables, wearables and IoT connected devices.